Design of an Interactive Quiz Management System for Early Childhood Learning Using Object-Oriented Programming in a Desktop-Based Application - Subiksa, Gde Brahupadhya; Peling, Ida Bagus Adisimakrisna; Pasek Agus Ariawan, Made (Jurnal Sistem Informasi Bisnis, 2025)
This study focuses on developing a more engaging and interactive quiz system for early childhood education based on a desktop platform (to prevent children from using gadgets directly). It implements four elements of early childhood learning theories: the theory of knowledge, the theory of development, the theory of learning, and the theory of teaching. The research and system development consist of three main stages. The first stage, data collection, aims to gather useful information for research and system development. The second stage involves system development using the waterfall model, implementing object-oriented programming in the Java desktop-based coding process. The final stage is system testing, conducted directly by its users (kindergarten teachers) to gather user experience information based on fundamental early childhood learning theories. The results of this study indicate that the quiz system can be built using Java programming based on object-oriented programming with a desktop application platform, ensuring that young children do not directly use the devices. Instead, teachers play a role in the teaching and learning process to help children focus more on the quiz. According to early childhood teaching theories, the quiz management system (QMS) helps young children develop awareness, thinking skills, and object understanding. Additionally, QMS supports the social growth and development of children by solving problems through quizzes, as well as helping them acquire general knowledge and basic skills.